Anorectal volume–pressure relations, contraction work, and flow during defecation - Gregersen, Hans; Wang, Yanmin; Field, Fred; Wang, Mengjun; Lo, Kar Man; Guo, Xiaomei; Combs, William; Kassab, Ghassan S. (Biomechanics and modeling in mechanobiology, 2022)
Fecobionics is an integrated device that has shown promise for assessment of anorectal function. We used a wireless Fecobionics prototype to visualize defecatory patterns and to compute volume–pressure, contraction work, and flow. Twelve normal subjects were studied. The probe was 10 cm-long and contained pressure sensors and electrodes for impedance planimetry. Pressures, diameters, and volume data during defecation were analyzed. The bag was distended inside rectum to the urge-to-defecate level where after the subjects were asked to evacuate. The contraction work and defecatory flow were computed from the volume changes during expulsion. The minimum anal diameter during the evacuation was 17.6 ± 1.5 mm. The middle diameter recording was 10–20% lower than the front diameter channels and 10–20% bigger than the rear channels. The bag volume at urge correlated with the minimum diameter ( r = 0.63). The diameter-pressure and volume–pressure loops were counterclockwise with phases of bag filling, isometric contraction, ejection and anal passage. The defecatory contraction work was 3520 ± 480 mL × cmH 2 O. The maximum flow during defecation was 302 ± 33 mL/s. The flow was associated with the anal diameter ( r = 0.84) but not with the rectoanal pressure gradient ( r = 0.14). Volume–pressure loops have a tremendous impact on the understanding of cardiopulmonary pathophysiology. Future studies will shed light on potential clinical impact in defecatory pathophysiology.